Effect of aggression on the performance of handball female players of Sargodha - Kousar, R.; Jabeen, A.; Qureshi, B. A. (Global Educational Studies Review, 2022)
The aim of this research was to examine the psychological factor of aggression influencing the female performance of the handball team in the Sargodha District. Taking this research objective as a general purpose of this study, a descriptive survey design was applied to examine the research issue. The samples for the present study included all female players of Handball in Sargodha District female colleges who were selected by using a stratified random sampling technique. A total of 52 handball players (age b/w 16 - 22 years) were taken as a sample. Two categories of questions were asked about aggression and performance. The aggression inventory scale was made to analyze the aggression level. Team performance was evaluated to measure the self-scoring. With respect to aggression scores in handball a considerable difference was noticed (t=-4.96, p<0.05) at the significance level (05%). The study results found that female players on Handball team had increased aggression. The current study also proved that there is a positive correlation between aggression and players' performance as positive reinforcement and winning the match have a good influence on the handball players' performance.